Hematopoietic Stem Cells in Type 1 Diabetes - Pastore, Ida; Assi, Emma; Ben Nasr, Moufida; Bolla, Andrea Mario; Maestroni, Anna; Usuelli, Vera; Loretelli, Cristian; Seelam, Andy Joe; Abdelsalam, Ahmed; Zuccotti, Gian Vincenzo; D’Addio, Francesca; Fiorina, Paolo (Frontiers in Immunology, 2021)
Despite the increasing knowledge of pathophysiological mechanisms underlying the onset of type 1 diabetes (T1D), the quest for therapeutic options capable of delaying/reverting the diseases is still ongoing. Among all strategies currently tested in T1D, the use of hematopoietic stem cell (HSC)-based approaches and of teplizumab, showed the most encouraging results. Few clinical trials have already demonstrated the beneficial effects of HSCs in T1D, while the durability of the effect is yet to be established. Investigators are also trying to understand whether the use of selected and better-characterized HSCs subsets may provide more benefits with less risks. Interestingly, ex vivo manipulated HSCs showed promising results in murine models and the recent introduction of the humanized mouse models accelerated the translational potentials of such studies and their final road to clinic. Indeed, immunomodulatory as well as trafficking abilities can be enhanced in genetically modulated HSCs and genetically engineered HSCs may be viewed as a novel “biologic” therapy, to be further tested and explored in T1D and in other autoimmune/immune-related disorders.